Mutation of the Atypical Kinase ABC1K3 Partially Rescues the PROTON GRADIENT REGULATION 6 Phenotype in Arabidopsis thaliana - Pralon, Thibaut; Collombat, Joy; Pipitone, Rosa; Ksas, Brigitte; Shanmugabalaji, Venkatasalam; Havaux, Michel; Finazzi, Giovanni; Longoni, Paolo; Kessler, Felix (Frontiers in Plant Science, 2020)
Photosynthesis is an essential pathway providing the chemical energy and reducing equivalents that sustain higher plant metabolism. It relies on sunlight, which is an inconstant source of energy that fluctuates in both intensity and spectrum. The fine and rapid tuning of the photosynthetic apparatus is essential to cope with changing light conditions and increase plant fitness. Recently PROTON GRADIENT REGULATION 6 (PGR6-ABC1K1), an atypical plastoglobule-associated kinase, was shown to regulate a new mechanism of light response by controlling the homeostasis of photoactive plastoquinone (PQ). PQ is a crucial electron carrier existing as a free neutral lipid in the photosynthetic thylakoid membrane. Perturbed homeostasis of PQ impairs photosynthesis and plant acclimation to high light. Here we show that a homologous kinase, ABC1K3, which like PGR6-ABC1K1 is associated with plastoglobules, also contributes to the homeostasis of the photoactive PQ pool. Contrary to PGR6-ABC1K1, ABC1K3 disfavours PQ availability for photosynthetic electron transport. In fact, in the abc1k1/abc1k3 double mutant the pgr6(abc1k1) the photosynthetic defect seen in the abc1k1 mutant is mitigated. However, the plastoquinone concentration in the photoactive pool of the double mutant is comparable to that of abc1k1 mutant. An increase of the PQ mobility, inferred from the kinetics of its oxidation in dark, contributes to the mitigation of the pgr6(abc1k1) photosynthetic defect. Our results also demonstrate that ABC1K3 contributes to the regulation of other mechanisms involved in the adaptation of the photosynthetic apparatus to changes in light quality and intensity such as the induction of thermal dissipation and state transitions. Overall, we suggests that, besides the absolute concentration of PQ, its mobility and exchange between storage and active pools are critical for light acclimation in plants.